Behavioral Phenotyping and Pathological Indicators of Parkinson's Disease in C. elegans Models - Maulik, Malabika; Mitra, Swarup; Bult-Ito, Abel; Taylor, Barbara E.; Vayndorf, Elena M. (Frontiers in Genetics, 2017)
Parkinson’s disease (PD) is a neurodegenerative disorder with symptoms that progressively worsen with age. Pathologically, PD is characterized by the aggregation of α-synuclein in cells of the substantia nigra in the brain and loss of dopaminergic neurons. This pathology is associated with impaired movement and reduced cognitive function. The etiology of PD can be attributed to a combination of environmental and genetic factors. A popular animal model, the nematode roundworm Caenorhabditis elegans, has been frequently used to study the role of genetic and environmental factors in the molecular pathology and behavioral phenotypes associated with PD. The current review summarizes cellular markers and behavioral phenotypes in transgenic and toxin-induced PD models of C. elegans.